Notes on the distribution of Anadendrum latifolium (Araceae) in India and its lectotypification - Rasingam, Ladan; Karthigeyan, Kaliyamurthy (Phytotaxa, 2021)
Anadendrum latifolium is reported here as new addition to the flora of India from Andaman & Nicobar Islands and a lectotype is designated from the existing type materials.